THE SANDMAN, BY E.T.A. HOFFMANN, AND CAPITAIN MENDONCA, BY MACHADO DE ASSIS: APPROACHES AROUND THE FANTASTIC GENRE - Pagnan, Celso Leopoldo [UNESP]; Santos, Adilson dos; Gretter Nishiura, Carla Aparecida (Univ Estado Mato Grosso, 2019)
This paper aims to reflect on the fantastic in literature, particularly the of the nineteenth century. We refer Todorov. We analyze two tales, in which there is an intertextual approach, either by topic or by the dialogue established. We analyze The Sandman, by Hoffmann, and Captain Mendonca, by Machado de Assis. We seek to show that while the Brazilian writer have a written a new tale, sought dialogue with the tale of the German writer. The essential point of the analysis was to demonstrate why these tales are classified as texts fantastic. We sought to determine the specific meaning of each tale.
Keywords: Fantastic; Hoffmann; Machado de Assis